Concomitant Presentation of Dengue Hemorrhagic Fever with Guillain-Barré Syndrome (GBS) - Nath, Jishu Deb; Bhowmik, Mitu; Nayem, Nakibul Hasan; Mamun, Abdullah Al (Journal of Bangladesh College of Physicians and Surgeons, 2023)
Guillain- Barre syndrome (GBS) is one of the rare complications in Dengue .We report a uncommon presentation as simultaneous onset of Dengue Haemorrhagic fever (DHF) with GBS. 29 year old student presented with bilateral weakness of lower legs after 2 days onset of fever and he was admitted and treated as DHF, Later he was diagnosed as GBS on the basis of areflexia and Nerve conduction study. He was recovered gradually and given only physiotherapy. J Bangladesh Coll Phys Surg 2023; 41: 88-91